Geography of FDI from Visegrad Countries in Russia - Kuznetsov, Alexey V.; Nevskaya, Anastasia A. (Bulletin of Geography. Socio-economic Series, 2017)
The article investigates the Russian place in outward FDI geography of the Visegrad countries. The role of the neighborhood effect is shown. With the help of the authors’ special methodology for FDI calculations which overcomes deficiencies in the Bank of Russia’s statistics, the distribution of the Visegrad group’s FDI between Russian regions is studied. The authors demonstrate the presence of a hierarchical-wave model of spatial diffusion of FDI by investors in retail and banking. At the same time, it is found that Moscow and its surrounding dominate the recipient regions. It is also shown that Visegrad group investments in Russia are mostly made by enterprises which remove any political component. As a result, their FDI expansion to the Russian market is likely to continue as soon as the Russian economy returns to growth .